Optimasi Kekasaran Permukaan Pada Material Amutit Dengan Proses CNC Turning Menggunakan Desain Taguchi - Zaldy Kurniawan; Eko Yudo; Ridho Rosmansyah (Manutech : Jurnal Teknologi Manufaktur, 2018)
Minimum surface roughness results are a desirable objective in the CNC NLX 2500 Y process, a precise adjustment of CNC NLX 2500 Y process parameters should be obtained in order to obtain minimal roughness of the workpiece surface. The research has been conducted to determine the contribution ofCNC NLX Y 2500 process parameters to reduce the variation of the work surface roughness response simultaneously. And the determination of the exact setting of CNC NLX Y 2500 process parameters in order to obtain minimal roughness of the workpiece surfaces. parameters of machining process are variedspindle rotation, cutting speed, the dept of cut. The experimental design is based on the Taguchi method and is an orthogonal matrix L8 (2³). The optimization method used is Taguchi. The experiment was conducted randomly with replication 2 times to overcome the disturbance factor that occurred during machining process. The results showed that to reduce the variation of the response simultaneously, the the dept of cut has the largest contribution, that is 82.6%, the spindle speed has a contribution percentage of 61.9%, the cut rate has a contribution percentage of 9.2%. To obtain a surface roughness of the workpiece is minimal, the spindle rotation is set at 2866 rpm, the cutting speed is set to 0.40 mm / rotation, the dept of cut is set to 1 mm.